2003
DOI: 10.1023/a:1025448620558
|View full text |Cite
|
Sign up to set email alerts
|

Chemomodulatory Influence of Ferula asafoetida on Mammary Epithelial Differentiation, Hepatic Drug Metabolizing Enzymes, Antioxidant Profiles and N-methyl-N-Nitrosourea-Induced Mammary Carcinogenesis in Rats

Abstract: The present study was conducted to ascertain the modulatory influences of Ferula asafoetida L. (asafoetida, flavoring agent) on the mammary epithelial tissue differentiation, hepatic drug metabolizing enzymes, antioxidant profiles and N-methyl-N-nitrosourea (MNU)-induced mammary carcinogenesis in Sprague-Dawley rats. Feeding with two doses of asafoetida (1.25 and 2.5% w/w in diet) showed a remarkable increase in the development and differentiation of ducts/ductules (p < 0.01-0.005), lobules (p < 0.005) and a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 21 publications
3
37
0
1
Order By: Relevance
“…MNU is a potent chemical carcinogen [25,26] and is widely used to induce mutations and carcinomas [27]. In this mouse endometrial carcinoma model, carcinoma developed within a relatively short time period (20- 30 weeks); thus, this model is convenient for the analysis of endometrial carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MNU is a potent chemical carcinogen [25,26] and is widely used to induce mutations and carcinomas [27]. In this mouse endometrial carcinoma model, carcinoma developed within a relatively short time period (20- 30 weeks); thus, this model is convenient for the analysis of endometrial carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to differences in the route and dose, and duration of E2 administration, or the effects of progesterone in mice with ovaries. MNU reportedly evokes not only various types of DNA damage [25][26][27], but also MSI and subsequent point mutations [30][31][32]. A previous study reported that an intraperitoneal injection of MNU into CD mice resulted in the development of thymic lymphoma and systemic MSI [30], suggesting that MNU impairs MMR function.…”
Section: Discussionmentioning
confidence: 99%
“…The oleo-gum resins obtained from this genus are of importance, and have been in use in folk medicine for centuries for curing many human ailments. Also, it was shown that Ferula asafoetida has potent antioxidant activity and can afford protection against free radical-mediated diseases such as carcinogenesis (Malli-Karjuna et al, 2003). A literature survey showed that no study has been done on antioxidative stress activity of F. szovitsiana DC.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers proved its efficacy in gastric ailments [71] such as ulceration, gastric irritation, and acid peptic diseases. It is also being used as an antispasmodic and digestive [72]. Apart from that, it is a potent anti-oxidant and Anticancer agent especially for the breast cancer and also possess antifungal activity (Fatehi et al).…”
Section: Quercus Infectoriamentioning
confidence: 99%